1998
DOI: 10.1172/jci119881
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of AT1 receptor mRNA and protein in normal placenta and its reduced expression in intrauterine growth restriction. Angiotensin II stimulates the release of vasorelaxants.

Abstract: Angiotensin II (ANG II) is a potent vasoconstrictor and growth promoter. Quantitative receptor autoradiography using the nonselective radioligand [125I]ANG II and subtype-selective competing compounds demonstrated the presence of both ANG II receptor (AT)1 and AT2 receptor recognition sites. In addition, a relatively small population of apparently non-AT1/non-AT2 sites was identified that may represent a novel high affinity ANG II recognition site in human placenta. Using placental membrane preparations, the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 47 publications
(48 reference statements)
5
80
0
2
Order By: Relevance
“…There was no difference in AT 2 receptor density between normal and preeclamptic tissues consistent with several previously studies. 22,41,44 In addition, mRNA levels of the Mas receptor, a reported Ang-(1-7) receptor, 45 were lower in preeclamptic than normal chorionic villi. Low levels of the Mas receptor were also observed with the measurement of AT 1-7 receptor density by autoradiography; however, there was no difference in the density between normal and preeclamptic chorionic villi.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in AT 2 receptor density between normal and preeclamptic tissues consistent with several previously studies. 22,41,44 In addition, mRNA levels of the Mas receptor, a reported Ang-(1-7) receptor, 45 were lower in preeclamptic than normal chorionic villi. Low levels of the Mas receptor were also observed with the measurement of AT 1-7 receptor density by autoradiography; however, there was no difference in the density between normal and preeclamptic chorionic villi.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that ANG II mainly binds to AT 1 receptor and elicits downstream vasocontrictor effects in the placenta. Li X et al [23] examined AT 1 and AT 2 receptor expression in PE and normal placental trophoblast cells and found that both receptors are present in the placenta and that AT 1 receptor predominates [23]. However, Li and colleagues observed that in placentas from PE and intrauterine growth restriction pregnancies the AT 1 receptor expression is decreased compared to normal placental expression.…”
Section: Discussionmentioning
confidence: 99%
“…Receptors for ANG II [2,6,[22][23][24][25], TX [26,27], and ET [28] are present in placental trophoblasts and vasculature. However, the differential effects of each vasoconstrictor in the regulation of placental vasomotor tone have not been simultaneously studied.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that both AT1 and AT2 receptors are present in placental tissues [19,20]. To further examine AT1 and AT2 receptor expression on placental vessel cells, VSMCs were exposed to placental conditioned medium for 30 min, 2 h and 4 h. Total cellular protein was extracted and protein expressions were then determined by Western blot analysis.…”
Section: At2 But Not At1 Receptor Expression Is Inducible In Placenmentioning
confidence: 99%